2001
DOI: 10.1210/en.142.11.5015
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Induction of SOCS Gene Expression by PRL

Abstract: The mechanisms whereby tissue sensitivity to PRL is controlled are not well understood. Here we report that expression of mRNA and protein for members of the SOCS/CIS/JAB family of cytokine signaling inhibitors is increased by PRL administration in ovary and adrenal gland of the lactating rat deprived of circulating PRL and pups for 24 h but not in mammary gland. Moreover, suckling increases SOCS mRNA in the ovary but not in the mammary gland of pup-deprived rats. Deprivation of PRL and pups for 48 h allows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
20
1
Order By: Relevance
“…These are also known to induce substantial SOCS-1 -3 and CIS gene expression (Adams et al, 1998;Tam et al, 2001). The presence of GH and PRL receptors in both epithelial and stromal cells has been previously shown in the normal human breast and in various benign and malignant human breast disorders (Clevenger et al, 1995;Mertani et al, 1998;Gebre-Medhin et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…These are also known to induce substantial SOCS-1 -3 and CIS gene expression (Adams et al, 1998;Tam et al, 2001). The presence of GH and PRL receptors in both epithelial and stromal cells has been previously shown in the normal human breast and in various benign and malignant human breast disorders (Clevenger et al, 1995;Mertani et al, 1998;Gebre-Medhin et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…for 20 min. Protein samples (100 mg) were immunoblotted as previously described (Tam et al, 2001). After semidry transfer, nitrocellulose membranes were blocked with TBS (pH 8.0) containing 5% skim milk, 0.1% Tween 20 and probed with goat anti-CIS antibody (1 : 250, Santa Cruz Biotechnology; cat.…”
Section: Immunoblotmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo studies have shown that PRL stimulated SOCS-3 expression in murine liver (Pezet et al 1999) and adipose tissue (Ling & Billig 2001) as well as in rat ovaries, mammary glands and adrenal glands (Tam et al 2001). In addition, PRL stimulated SOCS-3 expression in murine adipose tissue in vitro (Ling & Billig 2001).…”
Section: Introductionmentioning
confidence: 98%